Effects of maternal and lactational exposure to 2-hydroxy-4-methoxybenzone on development and reproductive organs in male and female rat offspring - Nakamura, Noriko (Birth Defects Res B Dev Reprod Toxicol, 2015)
BACKGROUND: 2-hydroxy-4-methoxybenzophenone (HMB) is an ultraviolet (UV)-absorbing compound used in many cosmetic products as a UV-protecting agent and in plastics for preventing UV-induced photodecomposition. HMB has been detected in over 95% of randomly collected human urine samples from adults and from premature infants, and it may have estrogenic potential. METHODS: To determine the effects of maternal and lactational exposure to HMB on development and reproductive organs of offspring, time-mated female Harlan Sprague-Dawley rats were dosed with 0, 1,000, 3,000, 10,000, 25,000, or 50,000 ppm HMB (7-8 per group) added to chow from gestation day 6 until weaning on postnatal day (PND) 23. RESULTS AND CONCLUSION: Exposure to HMB was associated with reduced body and organ weights in female and male offspring. No significant differences were observed in the number of implantation sites/litter, mean resorptions/litter, % litters with resorptions, number and weights of live fetuses, or sex ratios between the control and HMB dose groups. Normalized anogenital distance in male pups at PND 23 was decreased in the highest dose group. Spermatocyte development was impaired in testes of male offspring in the highest dose group. In females, follicular development was delayed in the highest dose group. However, by evaluating levels of the compound in rat serum, the doses at which adverse events occurred are much higher than usual human exposure levels. Thus, exposure to less than 10,000 ppm HMB does not appear to be associated with adverse effects on the reproductive system in rats.